2019
DOI: 10.2147/cmar.s191681
|View full text |Cite
|
Sign up to set email alerts
|

<p>KIF15 promotes bladder cancer proliferation via the MEK&ndash;ERK signaling pathway</p>

Abstract: Background Bladder cancer (BC) is the most common cancer of the urinary tract and invariably predicts a poor prognosis. In this study, we found a reliable gene signature and potential biomarker for predicting clinical prognosis. Methods The gene expression profiles were obtained from the GEO database. By performing GEO2R analysis, numerous differentially expressed genes (DEGs) were found. Three different microarray datasets were integrated in order to more precisely ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Although the structure and molecular functions of KIF15 have been studied for approximately 10 years, the role of KIF15 in the tumorigenesis and progression of OC has not yet been illuminated. A previous study had reported that KIF15 promoted the proliferation of cancer cells in pancreatic cancer [16], bladder cancer [17], breast cancer [18], and osteosarcoma [19]. It indicated that KIF15 was a proliferation-related biomarker in multiple malignancies, which we had veri ed on ovarian cancer in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Although the structure and molecular functions of KIF15 have been studied for approximately 10 years, the role of KIF15 in the tumorigenesis and progression of OC has not yet been illuminated. A previous study had reported that KIF15 promoted the proliferation of cancer cells in pancreatic cancer [16], bladder cancer [17], breast cancer [18], and osteosarcoma [19]. It indicated that KIF15 was a proliferation-related biomarker in multiple malignancies, which we had veri ed on ovarian cancer in this study.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have proposed that KIFs play important roles in different diseases even various of cancers. It can lead to congenital thrombocytopenia, breast cancer, oral cancer and bladder cancer [8,[23][24][25][26]. Recently, KIF15 has been reported to be highly expressed in gastrointestinal (GI) track cancers such as pancreatic cancer and hepatocellular cancer [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…KIF15 mediated pancreatic cancer proliferation through regulating the cell cycle and apoptosis [22]. KIF15 may be a potential prognostic biomarker in bladder cancer [23]. RNF113A expression is correlated with a poor prognosis of esophageal squamous cell carcinoma [24].…”
Section: Discussionmentioning
confidence: 99%